ArchSPL-MDD: An ADL-Based Model-Driven Strategy for Automatic Variability Management - Medeiros, Ana Luisa; Cavalcante, Everton; Batista, Thais; Silva, Eduardo (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2015)
Model-driven strategies have been used in the development of software product lines (SPLs) to facilitate product customization and to generate the source code of the derived products through variability management. In this context, the architecture description of the SPL is essential to make it clear how the architecture realizes the feature model and to represent both domain and application engineering architectural artifacts. Moreover, it is important to establish the association between the architectural specification and the artifacts involved in the SPL development process towards code generation. In this paper, we present Arch SPL-MDD, a model-driven strategy to support explicit modeling and automatic management of variabilities in SPLs. Arch SPL-MDD is associated to a generic process with systematic activities aimed to generate customized source code from the product configuration. Furthermore, the proposed strategy uses the Light PL-ACME architecture description language to support the architectural specification of the SPL, which is input of model transformations towards automatically generating SPL products. To evaluate the efficiency and applicability of Arch SPL-MDD, we conducted a controlled experiment by using Ginga For All, an SPL for the Ginga digital TV middleware.